2010
DOI: 10.1097/jgp.0b013e3181cc0314
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of African Americans and Asian Americans With Late-Life Depression and Mild Cognitive Impairment

Abstract: Objective-The purpose of this study was to compare the relative effectiveness of several different strategies for recruiting elderly Asians, African Americans, and Caucasians to participate in mental health research.Participants-A total of 35 African American, 24 Asian American, and 215 Caucasian participants were phone-screened for potential enrollment into a University of California, San Francisco Department of Psychiatry treatment outcome study for older adults (60+ years of age) with major depression and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This discrepancy is probably due to a lack of help-seeking in mental health settings by this demographic group (Bistricky et al, 2010). Recruitment of older African Americans was increased using a consumer-centered approach, which included building relationship with gate-keepers within the community who gained the trust of participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy is probably due to a lack of help-seeking in mental health settings by this demographic group (Bistricky et al, 2010). Recruitment of older African Americans was increased using a consumer-centered approach, which included building relationship with gate-keepers within the community who gained the trust of participants.…”
Section: Resultsmentioning
confidence: 99%
“…Bistricky and colleagues observed that older African Americans were less likely to be recruited into research studies through mental health sources than through non-mental health sources. This discrepancy is probably due to a lack of help-seeking in mental health settings by this demographic group (Bistricky et al, 2010). Recruitment of older African Americans was increased using a consumer-centered approach, which included building relationship with gatekeepers within the community who gained the trust of participants.…”
Section: Researchmentioning
confidence: 99%
“…The potential cultural stigma associated with a diagnosis of dementia (Hinton et al, 2000) may inhibit patients from complaining to their physicians about cognitive changes or may inhibit families from bringing up these issues for fear of insulting an older family member or a perceived head of the household. In support of this concern, prior studies have suggested that East Asian immigrants are less likely to seek mental health services and recommend them to others (Barry & Grilo, 2002), and a recent study indicated that Asian Americans were less likely than Caucasians to be referred to mental health research through traditional mental health pathways (Bistricky, Mackin, Chu, & Arean, 2010). In contrast, more advanced dementia is often associated with disruptive behavioral problems (J. C. Chen, Borson, & Scanlan, 2000), which often result in presentation to a physician for help with management.…”
mentioning
confidence: 99%
“…In our study, substantially more people recalled receiving the letter than the pamphlet. The mailing served as an introduction to the follow-up telephone contact in which trained culturally competent interviewers facilitated recruitment by conveying information and addressing low-literacy issues that may be more prevalent among older Latinos [15,19,20]. …”
Section: Discussionmentioning
confidence: 99%